RESOSIALISASI REMAJA PUTUS SEKOLAH DI PANTI SOSIAL BINA REMAJA BAMBU APUS JAKARTA - Musa, Hasrifah; Wibowo, Arif (Jurnal Pembangunan Manusia, 2020)
This paper discusses the implementation of the resocialization of school dropouts, the role of social workers, and obstacles arising in the PSBR Bambu Apus Jakarta. The study used a qualitative approach with descriptive research methods. The results of the study describe: (1) the implementation of the school's resocialization of dropouts in the PSBR Bambu Apus Jakarta includes internship supplies, the implementation of resocialization, and monitoring internships; (2) the role of social workers as a brokers, educators, mediators, enablers, group facilitator, analyst/evaluator; and (3) barriers arising include less optimal role assistance by social workers in the internship site, the time of limited internship activities, there is no cooperation letter in writing with the partner agency, the limitations of school dropouts, behavior and attitudes adolescent dropout of school that are not ready to adapt to their roles and responsibilities, lack of confidence adolescent dropout in serving customers, and the difference equipment used by PSBR Bambu Apus Jakarta with those used by the company in the internship activities.